Water emulsion type asphalt waterproof coating as well as preparation method and application thereof
By modifying carbonyl iron powder and fillers coated with silane layers, combined with polymer emulsions and a variety of fillers, the problems of construction slippage and insufficient weather resistance of water-emulsified asphalt waterproof coatings on vertical or inclined surfaces are solved, achieving good construction effects and weather resistance and extending service life.
Patent Information
- Application Number
- CN202511122769.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-12
- Publication Date
- 2025-09-26
AI Technical Summary
Existing water-emulsified asphalt waterproof coatings are prone to slipping when applied on vertical or inclined surfaces, have insufficient weather resistance, and have a short service life in harsh environments, making it difficult to meet waterproofing needs.
Modified carbonyl iron powder and silane-coated fillers are combined with polymer emulsion and various fillers to form a stable water-emulsified asphalt waterproof coating through physical adsorption, hydrogen bonding and chemical bonding, thereby improving the adhesion and weather resistance of the coating.
It improves the construction effect and weather resistance of the coating, enhances the anti-sagging and stability of the coating, extends its service life, and solves the waterproof problem of the coating in harsh environments.
Smart Images

Figure BDA0005543677070000021 
Figure BDA0005543677070000091 
Figure BDA0005543677070000101
Abstract
Description
Technical Field
[0001] The present invention relates to the field of waterproof coatings, in particular to an asphalt waterproof coating used on vertical surfaces or inclined surfaces, and specifically to a water-emulsified asphalt waterproof coating and a preparation method and application thereof. Background Art
[0002] Asphalt is a brown or dark brown organic cementitious material, an indispensable material in civil engineering construction. Asphalt waterproofing coatings are solvent-based or water-based waterproofing coatings formulated with asphalt as the base material. Solvent-based asphalt waterproofing coatings are made by dissolving the base asphalt directly in a solvent such as gasoline. Water-based asphalt waterproofing coatings are made by dispersing the base asphalt in water with a chemical or mineral emulsifier to form a stable aqueous dispersion. Amidst growing global environmental awareness, countries have introduced strict environmental regulations and standards to limit VOC emissions. Water-based asphalt waterproofing coatings use water as the dispersion medium, contain no organic solvents, or contain very low levels of organic solvents. They offer excellent environmental performance, comply with environmental regulations, and have been widely used in recent years.
[0003] However, ordinary water-emulsified asphalt waterproof coatings have poor mechanical properties. At the same time, for application requirements in harsh environments such as humidity, high temperature, and strong ultraviolet radiation, current water-emulsified asphalt waterproof coatings still have shortcomings and poor service life. In addition, for water-emulsified asphalt waterproof coatings used for waterproofing on vertical or inclined surfaces, there is obvious slippage, which is not conducive to thick coating and construction.
[0004] It should be noted that the information disclosed in the background section is only used to understand the background of the present application. Therefore, the background section of the present invention may include background information about the problem or environment of the present invention, but does not necessarily describe the prior art. Therefore, the content included in the background section does not constitute an admission by the applicant of prior art. Summary of the Invention
[0005] The purpose of the present invention is to overcome one or more deficiencies in the prior art and to provide an improved water-emulsifiable asphalt waterproof coating that can achieve better construction, weather resistance and waterproofing effects on vertical or inclined surfaces.
[0006] The present invention also provides a preparation method of a water-emulsified asphalt waterproof coating and its application as a waterproof coating on a vertical surface or an inclined surface.
[0007] In order to achieve the above object, a technical solution adopted by the present invention is:
[0008] A water-emulsified asphalt waterproof coating, the raw materials of which include emulsified asphalt and a polymer emulsion. The raw materials of the asphalt waterproof coating also include a first filler and a second filler, the first filler including oxides and / or salts of one or more elements selected from silicon, calcium, magnesium, and aluminum, the salts including carbonates and / or silicates, the second filler including modified carbonyl iron powder, the modified carbonyl iron powder including carbonyl iron powder and a silane layer located on the surface of the carbonyl iron powder, the silane layer and the carbonyl iron powder being bonded together by at least one or more of physical adsorption, hydrogen bonding, and chemical bonding; the mass ratio of the first filler to the second filler is 1:0.3-1.5.
[0009] In some embodiments of the present invention, based on the total mass of the emulsified asphalt, the polymer emulsion, the first filler and the second filler as 100%, the total feeding amount of the first filler and the second filler accounts for 20%-30%, for example, it can be 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, etc.
[0010] In some embodiments of the present invention, the first filler comprises a combination of multiple types selected from one of silicon dioxide, calcium carbonate, aluminum oxide, and magnesium silicate.
[0011] According to some specific aspects of the present invention, the first filler comprises a combination of one or more selected from talc powder, heavy calcium carbonate and mica powder.
[0012] Furthermore, the mesh size of the talcum powder is 400 to 800 meshes.
[0013] Furthermore, the mesh size of the heavy calcium carbonate is 600-800 meshes.
[0014] Furthermore, the mesh size of the mica powder is 600 to 1250 meshes.
[0015] In some embodiments of the present invention, based on the total mass of the emulsified asphalt, the polymer emulsion, the first filler and the second filler as 100%, the second filler accounts for 5%-15%, for example, it can be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, etc.
[0016] In some embodiments of the present invention, the modified carbonyl iron powder is prepared by reacting a compound represented by formula (I) with carbonyl iron powder, wherein the carbonyl iron powder contains hydroxyl groups on its surface;
[0017]
[0018] In formula (I), R1, R2, R3, and R4 are independently selected from C 1-10Alkyl, X is selected from O, a bond or CH2.
[0019] In the present invention, when X is selected from a bond, R2 is directly connected to Si.
[0020] In some embodiments of the present invention, the mass ratio of the compound represented by formula (I) to the carbonyl iron powder is 0.5-2:1.
[0021] In some embodiments of the present invention, the reaction is controlled to be carried out at 30-50° C. and / or the reaction is carried out in the presence of a catalyst, wherein the catalyst comprises aqueous ammonia. In some cases, the catalyst can be aqueous ammonia of a predetermined concentration prepared by mixing aqueous ammonia with deionized water at a relatively high concentration.
[0022] In some embodiments of the present invention, the average particle size of the carbonyl iron powder is 0.5 μm-20 μm, for example, 0.8 μm-16 μm, 1 μm-10 μm, or 2 μm-6 μm.
[0023] According to some specific aspects of the present invention, the method for preparing the modified carbonyl iron powder includes: adding the compound represented by formula (I) and ammonia water to the carbonyl iron powder in batches, heating and reacting, and generating the modified carbonyl iron powder after the reaction is completed.
[0024] Furthermore, in some specific cases, the method for preparing the modified carbonyl iron powder includes:
[0025] Slowly add the weighed carbonyl iron powder to anhydrous ethanol at a mass ratio of carbonyl iron powder to anhydrous ethanol of 1:3-5, and stir at a speed of 300-500 rpm for 30-60 minutes to uniformly disperse the carbonyl iron powder in the ethanol to obtain a carbonyl iron powder dispersion;
[0026] The method comprises the following steps: using a water bath to heat the mixture and continuously stirring the mixture, slowly dropping the compound represented by formula (I) into the carbonyl iron powder dispersion, wherein the mass ratio of the compound represented by formula (I) to the carbonyl iron powder is 0.5-2:1, and simultaneously slowly dropping an appropriate amount of a mixed solution of deionized water and ammonia water (the mass ratio of the mixed solution to the compound represented by formula (I) is 0.6-1.2:1) as a catalyst, wherein the concentration of the ammonia water is 25%-28%, and the volume ratio of deionized water to ammonia water is 5-10:1. The dropping speed is controlled and the addition is completed within 1 hour, and the temperature of the reaction system is maintained at 30°C-50°C. After the dropwise addition is completed, stirring is continued for 3-6 hours to allow the compound represented by formula (I) to hydrolyze and condense on the surface of the carbonyl iron powder to form a silane polymer film, thereby wrapping the carbonyl iron powder. In the actual reaction process, the intermediate product after the hydrolysis of the compound represented by formula (I) will react with the hydroxyl groups on the surface of the carbonyl iron powder and will also undergo a condensation reaction with itself, thereby forming a stable silane layer on the surface of the carbonyl iron powder;
[0027] After the reaction is completed, the product is centrifuged at a speed of 3000-5000 rpm for 5-10 minutes to separate the solid phase product, which is then washed with anhydrous ethanol and deionized water for 3-5 times, respectively. Finally, the product is dried in a vacuum drying oven at 60°C-80°C for 6-10 hours to evaporate the solvent and water, thereby obtaining a carbonyl iron powder coated with a silane polymer film, i.e., the modified carbonyl iron powder of the present invention.
[0028] In some embodiments of the present invention, R1, R2, R3, and R4 are independently selected from C 1-6 alkyl.
[0029] According to some specific aspects of the present invention, in formula (I), R1, R2, R3, and R4 are independently selected from methyl, ethyl, n-propyl, or isopropyl, and X is selected from O.
[0030] In some embodiments of the present invention, the compound represented by formula (I) is methyltrimethoxysilane, ethyltrimethoxysilane, methyltriethoxysilane, ethyltriethoxysilane, etc.
[0031] In some embodiments of the present invention, the emulsified asphalt comprises base asphalt, rubber elastomer particles, polyisobutylene, tackifying resin, water, emulsifier, softening oil and stabilizer.
[0032] According to some specific aspects of the present invention, the emulsified asphalt contains the following ingredients, in parts by weight: 30-40 parts of base asphalt, 3-5 parts of rubber elastomer particles, 5-8 parts of polyisobutylene, 5-10 parts of tackifying resin, 40-50 parts of deionized water, 1-3 parts of emulsifier, 3-5 parts of softening oil, and 0.1-1 part of stabilizer.
[0033] Furthermore, the matrix asphalt is selected from at least one of No. 90 and No. 70 heavy-duty matrix asphalt.
[0034] Furthermore, the rubber elastic particles are styrene-butadiene-styrene ternary block copolymer particles (SBS particles).
[0035] In some embodiments of the present invention, the styrene-butadiene-styrene terblock copolymer particles may be linear SBS particles.
[0036] Furthermore, the molecular weight of the polyisobutylene is 350-3500.
[0037] Furthermore, the tackifying resin is selected from at least one of C9 petroleum resin, C9 hydrogenated petroleum resin, coumarone resin and terpene resin.
[0038] Furthermore, the emulsifier is a compound of an anionic emulsifier and a nonionic emulsifier, wherein the weight ratio of the anionic emulsifier to the nonionic emulsifier is 1:0.4-0.8. Furthermore, the weight ratio of the anionic emulsifier to the nonionic emulsifier is 1:0.5-0.7.
[0039] In some embodiments of the present invention, the anionic emulsifier is selected from at least one of carboxylates, sulfonates, sulfates and phosphates. According to a specific aspect of the present invention, the anionic emulsifier is a sulfonate, for example, sodium dodecylbenzenesulfonate.
[0040] In some embodiments of the present invention, the nonionic emulsifier is selected from at least one of polyglycerol fatty acid esters, glycerides, polyethylene glycol and polyvinyl alcohol. According to a specific aspect of the present invention, the nonionic emulsifier can be polyvinyl alcohol.
[0041] Furthermore, the softening oil is selected from at least one of white oil, aromatic oil and naphthenic oil.
[0042] Furthermore, the stabilizer is selected from at least one of hydroxyethyl cellulose and hydroxypropyl methyl cellulose.
[0043] In some embodiments of the present invention, the emulsified asphalt is prepared by the following method:
[0044] (1) adding an emulsifier and a stabilizer to deionized water and stirring to prepare a soap solution, and adjusting the pH value of the soap solution to 10-12;
[0045] (2) heating and melting the matrix asphalt, adding rubber elastic particles, polyisobutylene, softening oil and tackifying resin weighed in a certain weight ratio, and shearing and stirring to obtain a premix;
[0046] (3) mixing and grinding the soap solution prepared in step (1) and the premix prepared in step (2).
[0047] Furthermore, in the process of preparing the emulsified asphalt, the implementation process of step (3) is: opening the colloid mill and the condensation device at the same time, pouring the soap solution prepared in step (1) and the premix prepared in step (2) into the colloid mill, mixing and grinding, and then opening the discharge valve to obtain the emulsified asphalt.
[0048] In some embodiments of the present invention, the polymer emulsion is a combination of one or more selected from styrene-butadiene latex, chloroprene latex, acrylic emulsion and ethylene-vinyl acetate latex.
[0049] In some embodiments of the present invention, the raw materials of the asphalt waterproof coating include, by weight: 40-65 parts of emulsified asphalt, 15-30 parts of polymer emulsion, 10-15 parts of first filler, 5-15 parts of second filler, and 0.1-0.3 parts of optional defoaming agent and 0.1-0.3 parts of optional preservative.
[0050] In some embodiments of the present invention, the defoaming agent is selected from at least one of polyoxyethylene polyoxypropylene pentaerythritol ether, polyoxyethylene polyoxypropanolamine ether and polyoxypropylene glycerol ether.
[0051] In some embodiments of the present invention, the preservative is an isothiazolinone preservative. Preferably, the preservative is selected from at least one of methylisothiazolinone and methylchloroisothiazolinone.
[0052] Another technical solution provided by the present invention is a method for preparing the water-emulsified asphalt waterproof coating described above, the preparation method comprising: mixing and homogeneously preparing the raw materials of the asphalt waterproof coating.
[0053] In some embodiments of the present invention, the preparation method of the water-emulsified asphalt waterproof coating comprises:
[0054] 1) Pour the above-mentioned emulsified asphalt, polymer emulsion, and preservative into a reactor, stir, and then add some defoamer; optionally, add 1 / 4-1 / 2 of the amount of defoamer;
[0055] 2) The first filler and the second filler are added to the reactor in batches, stirred, and then the remaining defoamer is added and stirred evenly to obtain the water-emulsified asphalt waterproof coating.
[0056] The water-emulsifiable asphalt waterproof coating product of the present invention exhibits creep properties and good adhesion, adapting to deformation and cracking of the base layer. Furthermore, the waterproof layer automatically heals after being damaged by external forces, preventing water leakage. This effectively addresses many challenges encountered in the application of existing waterproof materials, such as cracking, delamination, water leakage, and difficulty adapting to changes in the base layer. This material can be used as a standalone waterproof layer or combined with waterproof membranes to form a self-healing composite waterproof layer, enhancing the waterproofing effect.
[0057] Another technical solution provided by the present invention is the use of the above-mentioned water-emulsified asphalt waterproof coating as a waterproof coating on a vertical surface or an inclined surface.
[0058] In some embodiments of the present invention, during construction and use, the prepared water-emulsified asphalt waterproof coating is roller-coated, brushed, or sprayed onto a vertical surface or an inclined surface.
[0059] In some embodiments of the present invention, the vertical surface or the inclined surface may be the surface of a structural concrete base, and the pits, defects and cracks on the concrete surface may also be filled with the waterproof coating.
[0060] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:
[0061] The present invention addresses the problems of conventional water-emulsifiable asphalt waterproof coatings in the prior art, such as the tendency to slip when applied on vertical or inclined surfaces and insufficient weather resistance. The present invention innovatively provides an improved water-emulsifiable asphalt waterproof coating that can achieve better application, weather resistance, and waterproofing effects on vertical or inclined surfaces. Specifically, the present invention solves the above-mentioned problems by combining two fillers.
[0062] Furthermore, the above solution of the present invention is based on the accidental discovery of the inventors in the process of practice. When the inventors only used the first filler to prepare the water-emulsified asphalt waterproof coating, the improvement effect on the above problems in the prior art was not good. In order to pursue better weather resistance, the inventors creatively proposed to add carbonyl iron powder that can absorb ultraviolet rays and other external forces into the system to reduce the damage of ultraviolet rays to the waterproof coating, thereby improving the weather resistance of the coating; at the same time, in order to further improve the dispersibility of the carbonyl iron powder, the inventors of the present invention proposed to modify it with silane to obtain carbonyl iron powder wrapped in a silane layer, that is, modified carbonyl iron powder, and use it together with the first filler. At this time, it was found that:
[0063] On the one hand, compared with directly adding carbonyl iron powder, the carbonyl iron powder coated with the silane layer (also known as the silane polymer film) not only has improved dispersibility, but also the silane polymer film coating layer can effectively block the carbonyl iron powder from contact with air, moisture and other corrosive media during long-term storage and use of the carbonyl iron powder after silane treatment, thereby significantly improving the oxidation resistance and corrosion resistance of the carbonyl iron powder, allowing it to maintain good performance in harsh environments such as humidity, high temperature, and high salt, thereby extending the service life and application range of the coating product;
[0064] On the other hand, the silanol groups (-SiOH) generated by the hydrolysis of silane, such as the compound represented by formula (I), undergo condensation reactions with active groups such as hydroxyl and carboxyl groups in the polymer emulsion and asphalt to form a cross-linked structure. This cross-linking reaction can increase the cross-linking density between the polymer emulsion and asphalt, thereby improving its mechanical properties, water resistance, heat resistance, etc., thereby improving the performance of the coating;
[0065] In particular, the addition of silane polymer film coated carbonyl iron powder achieves the change of the rheological properties of the coating, and cooperates with the first filler to play a significant synergistic thickening effect, so that the anti-sagging performance of the waterproof coating of the present invention is greatly improved; after continuous research and mechanism analysis by the inventors, it is believed that the thickening mechanism should be: the polar functional groups (such as hydroxyl, amino, alkoxy) of the silane polymer film can produce multiple interfacial effects with the water phase, emulsifier molecules or asphalt particle surfaces in the emulsified asphalt system: the silane coating is hydrophilic (such as silicone hydroxyl), which can form hydrogen bonds with the water phase, and at the same time combine with the polar groups in the system (such as carboxyl and sulfonic acid groups of emulsifier molecules) through electrostatic attraction or hydrogen bonding, so that the coated carbonyl iron powder particles are more easily adsorbed on the surface of the asphalt particles, achieving a similar "bridging" effect, and The powder surface of the first filler usually also contains polar groups, such as a small amount of hydroxyl groups, which can also interact with the remaining hydroxyl groups on the surface of the modified carbonyl iron powder, and can also produce strong interfacial adsorption with the asphalt base material through hydrogen bonds and other forces, which is beneficial to their dispersion in the system and mutual cooperation. For example, it can form a shape similar to a physical skeleton, hindering the free flow of the coating; at the same time, the alkyl chain in the silane can produce van der Waals force with the oil phase core of the asphalt particles, further enhancing the interfacial bonding force between the particles and the asphalt particles. This close combination of "coated particles-asphalt particles" will cause the originally independently dispersed asphalt particles to be connected through the coated particles to form a chain or network aggregate of "asphalt particles-coated particles-asphalt particles", increasing the structural strength inside the system, hindering the flow, and thus playing a thickening role. In addition, the carbonyl iron powder has a small particle size (usually micron-level). After being coated with the silane polymer film, the apparent volume of the particles increases (core iron powder + coating layer), and the steric hindrance effect of the coating layer can reduce the agglomeration of the iron powder particles themselves, making them more evenly dispersed in the aqueous phase of the emulsified asphalt. The evenly dispersed coated particles will occupy part of the space in the aqueous phase, resulting in a reduction in the volume of the freely flowing "continuous phase" (water and dissolved emulsifier) in the system. The movement space of the asphalt particles and the coated particles is compressed, and the probability of mutual collision and friction is significantly increased. This increase in physical friction resistance directly leads to an increase in the viscosity of the system, which manifests as thickening. This can improve the anti-sagging and stability of the coating, making the coating easier to operate during construction on side walls or slopes. DETAILED DESCRIPTION
[0066] The above scheme is further described below in conjunction with specific examples; it should be understood that these examples are used to illustrate the basic principles, main features and advantages of the present invention, and the present invention is not limited to the scope of the following examples; the implementation conditions adopted in the examples can be further adjusted according to specific requirements, and the implementation conditions not specified are generally the conditions in routine experiments.
[0067] Unless otherwise specified in the following examples, all raw materials were purchased from commercial sources or prepared by conventional methods in the art.
[0068] Among the following, matrix asphalt was purchased from Xingtai Jitong Asphalt Sales Co., Ltd., model: national standard 70#; talc was purchased from Lingshou County Dexu Mining Co., Ltd., model: hsf-800; polyoxyethylene polyoxypropanolamine ether was purchased from Hubei Chengfeng Chemical Co., Ltd.; polyoxyethylene polyoxypropylene pentaerythritol ether was purchased from Jiangsu Hai'an Petrochemical Plant; hydroxyethyl cellulose was purchased from Jiangsu Pules Biotechnology Co., Ltd.; hydroxypropyl methylcellulose was purchased from Adamas, model: 89161O; polyvinyl alcohol was purchased from Adamas, model: 3301200BA; naphthenic oil, aromatic oil, and white oil were purchased from Guangzhou Mingen Petroleum Products Co., Ltd.; SBS particles were purchased from Dongguan Shenghao Plastic Raw Materials Co., Ltd., model: 3546; polyisobutylene was purchased from Guangzhou Huayang Chemical Co., Ltd. Co., Ltd., model: Daelim 2400 of South Korea; C9 petroleum resin was purchased from Shanghai Donghu Industrial Co., Ltd., model: Lanzhou Petrochemical C9; C9 hydrogenated petroleum resin was purchased from Foshan Ruisheng Plastic Co., Ltd., model: Eastman S1100; coumarone resin was purchased from Foshan Ruisheng Plastic Co., Ltd., model: Eastman C-115R; terpene resin was purchased from Chongqing Ruiya Biotechnology Co., Ltd., model: 9003-74-1; water-based acrylic emulsion was purchased from Badfu Group Co., Ltd., model: 7860; methyltrimethoxysilane was purchased from Adamas, model number: 16294B; carbonyl iron powder was purchased from Sichuan Xinjinchun Metal Materials Co., Ltd., brand: JC-Fe; polyacrylamide was purchased from Shanghai Yuanye Biotechnology Co., Ltd., model: S31321.
[0069] Example 1:
[0070] This example provides a water-emulsified asphalt waterproof coating and a preparation method thereof. The raw materials of the water-emulsified asphalt waterproof coating include, by weight: 65 parts of emulsified asphalt, 15 parts of polymer emulsion, 15 parts of first filler, 5 parts of second filler, 0.1 parts of defoamer, and 0.2 parts of preservative;
[0071] The polymer emulsion is water-based acrylic emulsion, the first filler is talc powder, the defoaming agent is polyoxyethylene polyoxypropanolamine ether, and the preservative is methylisothiazolinone.
[0072] The second filler is modified carbonyl iron powder, which is prepared by the following method: slowly adding weighed carbonyl iron powder to anhydrous ethanol at a mass ratio of carbonyl iron powder to anhydrous ethanol of 1:3, stirring at a speed of 500 rpm for 60 minutes to uniformly disperse the carbonyl iron powder in the ethanol to obtain a carbonyl iron powder dispersion;
[0073] Under continuous stirring, methyltrimethoxysilane is slowly added dropwise to the carbonyl iron powder dispersion, the mass ratio of methyltrimethoxysilane to carbonyl iron powder is 0.5-1, and at the same time, an appropriate amount of deionized water and ammonia mixture (the mass ratio of the mixture to methyltrimethoxysilane is 1:1) is slowly added dropwise as a catalyst, the concentration of ammonia is 25%, and the volume ratio of deionized water to ammonia is 10:1. The addition speed is controlled and the addition is complete within 1 hour. The temperature of the reaction system is maintained at 40°C. After the addition is completed, stirring is continued for 5 hours to allow the methyltrimethoxysilane to hydrolyze and condense on the surface of the carbonyl iron powder to form a layer of silane polymer film to achieve the encapsulation of the carbonyl iron powder;
[0074] After the reaction is completed, the product is centrifuged at a speed of 5000 rpm for 10 minutes to separate the solid phase product, which is then washed 5 times with anhydrous ethanol and deionized water respectively. Finally, the product is dried in a vacuum drying oven at 80°C for 10 hours to evaporate the solvent and moisture to obtain carbonyl iron powder coated with a silane polymer film, i.e., modified carbonyl iron powder.
[0075] In parts by weight, the emulsified asphalt contains: 30 parts of 70# base asphalt, 5 parts of SBS particles, 5 parts of polyisobutylene, 5 parts of tackifying resin, 50 parts of deionized water, 2 parts of emulsifier, 5 parts of softening oil, and 0.2 parts of stabilizer;
[0076] The tackifying resin is C9 petroleum resin; the emulsifier is composed of anionic emulsifier and nonionic emulsifier in a weight ratio of 1:0.6, the anionic emulsifier is sodium dodecylbenzenesulfonate, and the nonionic emulsifier is polyvinyl alcohol; the softening oil is white oil, and the stabilizer is hydroxypropyl methylcellulose.
[0077] Emulsified asphalt is prepared by the following method:
[0078] S1: Add the emulsifier and stabilizer to 50 parts of 50°C water and stir to prepare a soap solution. Then, adjust the pH value of the soap solution to 11±0.5 using an alkaline aqueous solution (saturated sodium hydroxide aqueous solution);
[0079] S2: Heat 70# base asphalt, then add SBS particles, polyisobutylene, white oil and C9 petroleum resin to the hot melt base asphalt, shear and stir to obtain a premix, and then place it in an oven for later use; the shear and stirring speed is 3000r / min;
[0080] S3: Open the colloid mill and the condensing device at the same time, pour the soap solution prepared in step S1 and the premix prepared in step S2 into the colloid mill, mix and grind them evenly, then open the discharge valve to obtain emulsified asphalt.
[0081] The water-emulsified asphalt waterproof coating is prepared by the following method: the emulsified asphalt, water-based acrylic emulsion, and methylisothiazolinone prepared above are taken according to the formula and poured into a reactor, stirred evenly, and then one-third of the formula amount of polyoxyethylene polyoxypropanolamine ether is added and mixed evenly; then the formula amount of talc powder and modified carbonyl iron powder are added to the reactor in three times, stirred, and then the remaining two-thirds of polyoxyethylene polyoxypropanolamine ether is added and stirred evenly to obtain the water-emulsified asphalt waterproof coating.
[0082] Example 2:
[0083] This example provides a water-emulsified asphalt waterproof coating and a preparation method thereof. The raw materials of the water-emulsified asphalt waterproof coating include, by weight: 60 parts of emulsified asphalt, 15 parts of polymer emulsion, 15 parts of first filler, 10 parts of second filler, 0.1 parts of defoamer, and 0.2 parts of preservative;
[0084] The polymer emulsion is water-based acrylic emulsion, the first filler is talc powder, the defoaming agent is polyoxyethylene polyoxypropylene pentaerythritol ether, and the preservative is methylisothiazolinone.
[0085] In parts by weight, the emulsified asphalt contains: 30 parts of 70# base asphalt, 5 parts of SBS particles, 5 parts of polyisobutylene, 5 parts of tackifying resin, 50 parts of deionized water, 2 parts of emulsifier, 5 parts of softening oil, and 0.2 parts of stabilizer;
[0086] The tackifying resin is C9 petroleum resin; the emulsifier is composed of anionic emulsifier and nonionic emulsifier in a weight ratio of 1:0.6, the anionic emulsifier is sodium dodecylbenzenesulfonate, and the nonionic emulsifier is polyvinyl alcohol; the softening oil is aromatic oil, and the stabilizer is hydroxyethyl cellulose.
[0087] Other details are the same as in Example 1.
[0088] Example 3:
[0089] This example provides a water-emulsified asphalt waterproof coating and a preparation method thereof. The raw materials of the water-emulsified asphalt waterproof coating include, by weight: 55 parts of emulsified asphalt, 15 parts of polymer emulsion, 15 parts of first filler, 15 parts of second filler, 0.1 parts of defoamer, and 0.2 parts of preservative;
[0090] The polymer emulsion is water-based acrylic emulsion, the first filler is talc powder, the defoaming agent is polyoxyethylene polyoxypropylene pentaerythritol ether, and the preservative is methylisothiazolinone.
[0091] In parts by weight, the emulsified asphalt contains: 30 parts of 70# base asphalt, 5 parts of SBS particles, 5 parts of polyisobutylene, 5 parts of tackifying resin, 50 parts of deionized water, 2 parts of emulsifier, 5 parts of softening oil, and 0.2 parts of stabilizer;
[0092] The tackifying resin is C9 petroleum resin; the emulsifier is composed of anionic emulsifier and nonionic emulsifier in a weight ratio of 1:0.6, the anionic emulsifier is sodium dodecylbenzenesulfonate, and the nonionic emulsifier is polyvinyl alcohol; the softening oil is aromatic oil, and the stabilizer is hydroxyethyl cellulose.
[0093] Other details are the same as in Example 1.
[0094] Comparative Example 1:
[0095] This example provides a water-emulsified asphalt waterproof coating and a preparation method thereof, which is basically the same as Example 1, with the only difference being that the second filler is not added and the addition amount of the first filler is adjusted to 20 parts.
[0096] Comparative Example 2:
[0097] This example provides a water-emulsifiable asphalt waterproof coating and a preparation method thereof, which is basically the same as Example 1, with the only difference being that the second filler is replaced with an equal weight of unmodified carbonyl iron powder.
[0098] Comparative Example 3:
[0099] This example provides a water-emulsified asphalt waterproof coating and a preparation method thereof, which is basically the same as Example 1, with the only difference being that the second filler is replaced with an associative polyurethane thickener commonly used in existing asphalt waterproof coatings.
[0100] Performance testing:
[0101] The performance of the water-emulsifiable asphalt waterproof coatings prepared in the examples of the present invention and the comparative examples was tested in accordance with the test methods in GB / T 16777-2008 "Test Methods for Building Waterproof Coatings", JC / T 408-2005 "Water-emulsifiable asphalt waterproof coatings", JC / T 1069-2008 "Base treatment agent for asphalt-based waterproof membranes", T / CECS10321-2023 "High-viscosity and anti-water-skid polymer asphalt waterproof coatings", and T / CECS10310-2023 "Water-based polyurethane waterproof coatings". The test results are shown in Table 1.
[0102] Table 1
[0103]
[0104]
[0105] By comparing Example 1 with Comparative Examples 1-2, it can be found that compared with the direct addition of carbonyl iron powder, the addition of silane polymer film-coated carbonyl iron powder after carbonyl iron powder coated with methyltrimethoxysilane can change the rheological properties of the coating during long-term storage and use, and play a significant synergistic thickening effect; the silane polymer film coating layer can effectively block the contact of carbonyl iron powder with air, moisture and other corrosive media, thereby significantly improving the oxidation resistance and corrosion resistance of carbonyl iron powder. At the same time, carbonyl iron powder can absorb external energy such as ultraviolet rays, reduce the damage of ultraviolet rays to waterproof coatings, thereby improving the weather resistance of the coating, so that it can still maintain good performance in harsh environments such as humidity, high temperature, and high salt, thereby extending the service life and scope of application of the coating product. In addition, the silanol groups (-SiOH) generated by the hydrolysis of methyltrimethoxysilane react with active groups such as hydroxyl and carboxyl groups in the polymer emulsion and asphalt to form a cross-linked structure. This cross-linking reaction can increase the cross-link density between the polymer emulsion and asphalt, thereby improving its mechanical properties, water resistance, heat resistance, etc., thereby improving the performance of the coating. In addition, as can be seen from Comparative Example 2, directly adding unmodified carbonyl iron powder may actually bring about adverse effects. Analysis suggests that this is probably because the carbonyl iron powder itself is prone to unexpected reactions such as rust during use, which damages the formed coating film, causing most of the mechanical properties to deteriorate and also insufficient long-term storage stability.
[0106] By comparing Example 1 and Comparative Example 3, it can be found that the thickening method of the present invention can effectively reduce the water absorption rate of the coating and the storage stability of the coating itself compared with ordinary thickeners on the market, while also improving various mechanical properties of the coating.
[0107] In addition, practice has found that since carbonyl iron powder is used as one of the raw materials in the waterproof coating system of the present invention, and due to its excellent dispersibility, it can be evenly dispersed in the system, therefore, other methods such as microwave heating can be used to accelerate the film formation speed of the waterproof coating, thereby reducing the construction cycle or waiting time. In particular, since it is evenly distributed with other raw materials in the waterproof system, after microwave heating, all coatings can obtain a similar drying speed, avoiding the generation of unexpected internal stress.
[0108] The above embodiments are intended only to illustrate the technical concepts and features of the present invention. Their purpose is to enable those skilled in the art to understand the contents of the present invention and implement them accordingly. They are not intended to limit the scope of protection of the present invention. Any equivalent changes or modifications made in accordance with the spirit of the present invention are intended to be covered by the scope of protection of the present invention.
[0109] The endpoints of the ranges and any values disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoints of each range, the endpoints of each range and individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered to be specifically disclosed herein.
Claims
1. A water-emulsion asphalt waterproof coating, whose raw materials include emulsified asphalt and polymer emulsion, characterized in that: The raw materials of the asphalt waterproof coating also include a first filler and a second filler, the first filler includes oxides and / or salts of one or more elements selected from silicon, calcium, magnesium, and aluminum, the salts include carbonates and / or silicates, the second filler includes modified carbonyl iron powder, the modified carbonyl iron powder includes carbonyl iron powder and a silane layer located on the surface of the carbonyl iron powder, the silane layer and the carbonyl iron powder are bonded together by at least one or more of physical adsorption, hydrogen bonds, and chemical bonds; the mass ratio of the first filler to the second filler is 1:0.3-1.
5.
2. The water-emulsion asphalt waterproof coating according to claim 1, characterized in that: Taking the total mass of the emulsified asphalt, the polymer emulsion, the first filler and the second filler as 100%, the total feed amount of the first filler and the second filler accounts for 20%-30%; and / or, the first filler comprises a combination of multiple ones selected from one of silicon dioxide, calcium carbonate, aluminum oxide, and magnesium silicate.
3. The water-emulsion asphalt waterproof coating according to claim 1, characterized in that: The first filler comprises a combination of one or more selected from talc powder, heavy calcium carbonate and mica powder, further, the mesh number of the talc powder is 400-800 mesh, the mesh number of the heavy calcium carbonate is 600-800 mesh, and the mesh number of the mica powder is 600-1250 mesh; and / or, based on the total mass of the emulsified asphalt, the polymer emulsion, the first filler and the second filler as 100%, the second filler accounts for 5%-15%.
4. The water-emulsion asphalt waterproof coating according to claim 1, characterized in that: The modified carbonyl iron powder is prepared by reacting a compound represented by formula (I) with carbonyl iron powder, wherein the surface of the carbonyl iron powder contains hydroxyl groups; In formula (I), R1, R2, R3, and R4 are independently selected from C 1-10 Alkyl, X is selected from O, a bond or CH2.
5. The water-emulsion asphalt waterproof coating according to claim 4, characterized in that: The mass ratio of the compound represented by formula (I) to the carbonyl iron powder is 0.5-2:1; and / or the reaction is controlled to be carried out at 30-50°C and / or the reaction is carried out in the presence of a catalyst, and the catalyst comprises aqueous ammonia; and / or the average particle size of the carbonyl iron powder is 0.5μm to 20μm.
6. The water-emulsion asphalt waterproof coating according to claim 4, characterized in that: The method for preparing the modified carbonyl iron powder comprises: adding the compound represented by formula (I) and ammonia water to the carbonyl iron powder in batches, heating and reacting, and generating modified carbonyl iron powder after the reaction is completed; and / or, in formula (I), R1, R2, R3, and R4 are independently selected from methyl, ethyl, n-propyl, or isopropyl, and X is selected from O.
7. The water-emulsion asphalt waterproof coating according to claim 1, characterized in that: The emulsified asphalt comprises base asphalt, rubber elastomer particles, polyisobutylene, tackifying resin, water, emulsifier, softening oil and stabilizer; Furthermore, the matrix asphalt is selected from at least one of No. 90 and No. 70 heavy-duty matrix asphalt; Furthermore, the rubber elastic body particles are styrene-butadiene-styrene ternary block copolymer particles; Furthermore, the molecular weight of the polyisobutylene is 350-3500; Furthermore, the tackifying resin is selected from at least one of C9 petroleum resin, C9 hydrogenated petroleum resin, coumarone resin and terpene resin; Furthermore, the emulsifier is a compound of an anionic emulsifier and a nonionic emulsifier, wherein the weight ratio of the anionic emulsifier to the nonionic emulsifier is 1:0.4-0.8; Furthermore, the softening oil is selected from at least one of white oil, aromatic oil and naphthenic oil; Furthermore, the stabilizer is selected from at least one of hydroxyethyl cellulose and hydroxypropyl methyl cellulose.
8. The water-emulsion asphalt waterproof coating according to claim 1, characterized in that: The emulsified asphalt comprises the following ingredients in parts by weight: 30-40 parts of base asphalt, 3-5 parts of rubber elastomer particles, 5-8 parts of polyisobutylene, 5-10 parts of tackifying resin, 40-50 parts of deionized water, 1-3 parts of emulsifier, 3-5 parts of softening oil, and 0.1-1 part of stabilizer; and / or, The emulsified asphalt is prepared by the following method: (1) adding an emulsifier and a stabilizer to deionized water and stirring to prepare a soap solution, and adjusting the pH value of the soap solution to 10-12; (2) heating and melting the matrix asphalt, adding rubber elastic particles, polyisobutylene, softening oil and tackifying resin weighed in a certain weight ratio, and shearing and stirring to obtain a premix; (3) mixing and grinding the soap solution prepared in step 1) and the premix prepared in step 2); and / or, The polymer emulsion is a combination of one or more selected from styrene-butadiene latex, chloroprene latex, acrylic emulsion and ethylene-vinyl acetate latex; and / or, In parts by weight, the raw materials of the asphalt waterproof coating include: 40-65 parts of emulsified asphalt, 15-30 parts of polymer emulsion, 10-15 parts of first filler, 5-15 parts of second filler, and 0.1-0.3 parts of optional defoaming agent and 0.1-0.3 parts of optional preservative.
9. A method for preparing the water-emulsified asphalt waterproof coating according to any one of claims 1 to 8, characterized in that: The preparation method comprises: mixing and evenly mixing the raw materials of the asphalt waterproof coating.
10. Use of the water-emulsified asphalt waterproof coating according to any one of claims 1 to 8 as a waterproof coating on a vertical surface or an inclined surface.